Developing Resilient Agriculture to Climate Change in India - Khatri-Chhetri, Arun; Sahin, Shehnab; Yadav, Akhilesh (2018)
This brochure highlights the aspects of a project collaboration between CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) South Asia and a private sector giant in India, ITC Limited. The project represents a convergence of ITC's 'Sunehra Kal' mission for promoting sustainable rural livelihoods in India, and CCAFS's Climate-Smart Village approach. The project has been launched in three climate vulnerable states of India- Rajasthan, Madhya Pradesh and Maharashtra.